A seventeen-year-old female with hepatosplenic T-cell lymphoma associated with parvoviral infection - Saadiya Haque; Ying Xiang; Metin Ozdemirli; Aziza Shad; Bhaskar Kallakury (MDPI AG, 2010)
Hepatosplenic T-cell lymphoma (HSTL) is rare, being derived from cytotoxic T-cells, and manifests as an extranodal systemic lymphoma. We present an unusual case of a seventeen-year-old female, with no significant prior medical history, presenting with a hepatosplenic T-cell lymphoma. The diagnosis was confirmed by histological examination, immunohistochemisty, and flow cytometry. A staging work-up demonstrated bone marrow involvement by HSTL with concomitant intranuclear parvoviral inclusions.